Kant trouble : the obscurities of the enlightened - Morgan, Diane, 1963- (Warwick studies in European philosophy., 2000)
"Kant Trouble" offers a highly original and incisive reading of some of the lesser known and less lucid aspects of Kantian thought. Diane Morgan focuses her investigation on a radical reappraisal of Kant's writings on architecture, monarchy and faith in progress. She challenges the widely held view of Kant as the exponent of concrete and rigid rationality, and argues that his airtight "architectonic" mode of reasoning, which Kant identified in "The Critique of Pure Reason," overlooks certain topics which destabilize it. Exploring such topics as temporary forms of architecture and the concept of radical evil, Morgan arrives at a fresh and ground-breaking perspective on Kant not as a concrete rationalist but as a daring thinker--willing to entertain subversive themes that threaten his own system and the humanistic legacy of the Enlightenment